Effect of Freezing Duration and Thawing Temperature on Fat Content in Expressed Breast Milk - Alexander Theo Yuda Salean; Subandrate Subandrate; Safyudin Safyudin (JURNAL KEBIDANAN, 2023)
One of the methods to keep working mothers able to provide breast milk is freezing. However, the processing carried out on breast milk can affect the nutritional content in it. Therefore, this study aims to see the effect of freezing duration and thawing temperature on fat content in expressed breast milk. This research was experimental research with pretest and posttest design. Breast milk from one mother was divided into 45 samples based on freezing duration and thawing temperature. The dependent variable in this study was the fat content of expressed breast milk, while the independent variables were freezing duration and thawing temperature of expressed breast milk. The fat content test used was the GPO-PAP method. Then the data were analyzed using one-way anova test and paired t-test. The average expressed breast milk fat content from initial levels, freezing 3 days, 7 days and 14 days and thawed at 4oC, 25oC and 37oC respectively were 178,679, 176,604, 175,849, 173,962, 71,698, 67,736, 66,415, 68,302, 66.038, 66.226 mg/dL. Based on the paired t-test, there was a decrease in fat content which had implications for the freezing duration of 7 days and 14 days with p=0.000 (p0.05). Meanwhile, based on the results of the one-way anova test, there was no difference in fat content based on variations in thawing temperature (4oC, 25oC, and 37oC) with p0.05. As a conclusion, there is an effect of freezing duration on fat content in expressed breast milk, whereas there is no effect of thawing temperature on fat content in expressed breast milk.